"Bond of love": the action of the Spirit - D. T. Williams (Acta Theologica)
The emergence of the various forms of Pentecostal and Charismatic theology has led to a welcome interest in the third Person of the Trinity, who has been largely neglected for centuries. However, while there has been a concentration on the experience of the Spirit, this has not been matched by an understanding of his work. The ancient idea, seen especially in Augustine, is that the main activity of the Spirit is that of providing relationship, as the “bond of love”; this provides a key concept which undergirds the work of the Spirit in creation, redemption, sanctification and empowering. It is hoped that increased understanding of the work of the Spirit will contribute to the healing of divisions in Christianity which emerged out of conflicting attitudes to the modern experiences.